The impact of photovoice on mental health and stigma: A systematic review and meta-analysis. - Adeniyi Adeboye; Ugochukwu Aghalu; Whitney Onuorah; Chizor Samuel-Nwokeji; Chimaobi Nwanguma; Adekunle Akerele; Judy Wasige (PLOS Global Public Health)
Photovoice is a transformative tool for improving health outcomes among people living with mental ill-health (PLWMI), fostering empowerment and social change. Only one meta-analysis has evaluated the effectiveness of photovoice for mental health outcomes. However, the study focused on various health conditions and only addressed two mental health outcomes. With an exclusive focus on mental health and stigma, this meta-analysis aimed to provide a comprehensive understanding of photovoice's impact on eight mental health and stigma-related outcomes in PLWMI and healthcare providers (HCPs). The study included seven randomised control trials (Sample size (n)=754), retrieved from electronic databases including Cochrane Trials, CINAHL Plus, ProQuest, Medline, PsychInfo, and Google Scholar, published between 2013 and 2023. Random-effects meta-analyses were conducted to calculate effect sizes (Cohen's d (d)). The study protocol was pre-registered on PROSPERO (CRD42023476867). Results showed significant improvements in mental health outcomes for PLWMI. Photovoice led to reductions in social withdrawal (n = 318; d, 95% CI = -0.20, -0.41 to 0.00) and depression (n = 267; d, 95% CI = -0.23, -0.45 to -0.02). Additionally, it increased self-efficacy (n = 267; d, 95% CI = 0.22, 0.00 to 0.44) and recovery (n = 285; d, 95% CI = 0.19, -0.02 to 0.41). However, there was a decrease in stigma resistance (n = 318; d, 95% CI = -0.13, -0.36 to 0.10). Among HCPs, there were significant improvements in both stigma and mental health-related outcomes, with reductions in anger (n = 330; d, 95% CI = -1.05, -2.79 to 0.69), social distance (n = 418; d, 95% CI = -1.41, -3.02 to 1.03), and the perception of danger (n = 115; d, 95% CI = -1.80, -5.04 to 1.44). The findings highlight the potential of photovoice as an effective intervention for improving mental health outcomes and reducing stigma in both PLWMI and HCPs. Consequently, photovoice can play a crucial role in enhancing the well-being of PLWMI and in transforming HCP attitudes within healthcare settings.